Islamic housing between yesterday and today = Perumahan Islam antara semalam dan hari ini - Omer, Spahic (International Islamic University Malaysia, 2017)
This paper discusses the quintessence of Islamic housing against the backdrop of some fundamental laws of history and civilization. It calls for properly comprehending and reviving the Islamic housing phenomenon within the context of studying the subjects of history and critical thinking. The paper concludes that the house institution occupies an extraordinary place in Islam. It is a family development centre and, as such, a microcosm of Islamic culture and civilization. The prospect of reviving Islamic housing is an arduous task. Its successful implementation will revolve around the following thrusts: creating a comprehensive built environment educational culture, upholding and integrating into the former the ideals of tawhid (Allah’s Oneness) and the rest of Islamic teachings and values, and introducing the principle of unreserved following in religion and unrestricted inventing in sheer worldly matters. The importance of studying history is discussed first. Then, the relationship between Islamic housing and critical thinking is dwelled on. And finally, in the light of the findings in the first two sections, some prerequisites for contemporary Islamic housing are discussed.